(untitled) (The New Uzbekistan Journal of Medicine, 2025)
The synthesis and study of polymer-metal complexes involving pectin and Group II metals play a vital role in the development of new, effective pharmaceutical agents for agriculture and medicine. The formation of such complexes not only reduces the toxicity of ligands but also enhances their immunological activity and positively influences the germination dynamics of agricultural crop seeds. Particularly important is the water solubility of polymer-metal complexes, which contributes to their biodegradability and expands their potential for practical application. In this study, polymer-metal complexes of pectin with calcium (Ca²⁺), magnesium (Mg²⁺), and zinc (Zn²⁺) ions were synthesized by mixing equimolar salt solutions with pectin at room temperature. Pectin, a weak acid, acts as a coordinating ligand through the lone pair electrons on the oxygen atoms in its carboxyl groups, forming stable coordination compounds with the metal ions. The physicochemical properties and potential applications of the resulting complexes were investigated.